A Literature Review on the Effectiveness of Manual and Mechanically Enhanced Irrigation Techniques in Root Canal Disinfection - Jader Oliva Jorge; Rafaela Regina de Lima; Kelly Oliva Jorge (Archives of Current Research International, 2025)
Aims: To compare the effectiveness of manual irrigation techniques with enhanced irrigation methods in the disinfection and cleaning of the root canal system in Endodontics. Study Design: Descriptive literature review. Place and Duration of Study: The review was conducted using scientific articles retrieved from the SciELO, PubMed, and LILACS databases, covering the period from February to August 2019. Methodology: A total of 45 scientific articles published between 1970 and 2019 were selected based on predefined eligibility criteria. The search included descriptors in Portuguese and English related to irrigation techniques in Endodontics. The selected studies focused on the performance of various irrigation methods, including manual irrigation with syringe and needle, Passive Ultrasonic Irrigation (PUI), the Easy Clean system, and the XP-Endo Finisher file. Results: Manual irrigation was found to be the least effective method for canal disinfection and debris removal. In contrast, activation techniques such as PUI, Easy Clean, and XP-Endo Finisher showed significantly better cleaning outcomes, especially in anatomically complex areas. Among them, the XP-Endo Finisher provided the most effective results in cleaning after instrumentation and final irrigation. Conclusion: Enhanced irrigation techniques, particularly those involving mechanical activation, significantly improve root canal cleaning compared to conventional methods. Nevertheless, manual irrigation remains a valuable tool when applied with appropriate solutions and clinical protocols. The choice of irrigation strategy should be guided by anatomical considerations and clinical objectives to ensure the success of endodontic treatment.